2014
DOI: 10.1158/1078-0432.ccr-13-3036
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing of Translocation Renal Cell Carcinoma Reveals Novel RNA Splicing Partners and Frequent Mutations of Chromatin-Remodeling Genes

Abstract: Purpose MITF/TFE translocation renal cell carcinoma (TRCC) is a rare subtype of kidney cancer. Its incidence and the genome-wide characterization of its genetic origin have not been fully elucidated. Experimental design We performed RNA and exome sequencing on an exploratory set of TRCC (n=7), and validated our findings using The Cancer Genome Atlas (TCGA) clear-cell RCC (ccRCC) dataset (n=460). Results Using the TCGA dataset, we identified 7 TRCC (1.5%) cases and determined their genomic profile. We disco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 31 publications
(40 reference statements)
4
109
1
3
Order By: Relevance
“…We analyzed our RNA-seq data to evaluate its usefulness for the discovery of new and known fusions in tRCC ( Supplementary Table 13 ). Of the samples classified as tRCC on the basis of morphology and TFE3 immunohistochemistry, we found evidence for the previously reported ASPSCR1-TFE3 fusion 25,70,71 and PRCC-TFE3 fusion 71 . We confirmed this result further using FISH analyses ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 77%
“…We analyzed our RNA-seq data to evaluate its usefulness for the discovery of new and known fusions in tRCC ( Supplementary Table 13 ). Of the samples classified as tRCC on the basis of morphology and TFE3 immunohistochemistry, we found evidence for the previously reported ASPSCR1-TFE3 fusion 25,70,71 and PRCC-TFE3 fusion 71 . We confirmed this result further using FISH analyses ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 77%
“…Cumulative studies have identified several gene fusion partners of TFE3 , including UBX domain containing tether for SLC2A4 ( ASPSCR1 ), proline‐rich mitotic checkpoint control factor ( PRCC ), and splicing factor proline and glutamine rich ( SFPQ ) . Less frequent fusion partners such as mediator complex subunit 15 ( MED15 ) and dishevelled segment polarity protein 2 ( DVL2 ) have also been identified . The histological diagnosis of Xp11 translocation RCCs is based on a characteristic morphology, such as papillary architecture composed of clear epithelioid cells with psammoma bodies, and strong nuclear immunostaining of TFE3.…”
Section: Introductionmentioning
confidence: 99%
“…Expression profiling studies had demonstrated that the MET receptor tyrosine kinase is induced by TFE3 gene fusions, and MET protein expression has been verified by immunohistochemistry; however, results of a clinical trial targeting MET in Xp11 translocation neoplasms have been disappointing [8]. Whole genome and RNA sequencing studies have demonstrated frequent mutations in chromatin remolding genes such as INOEBD in Xp11 translocation RCC, though this mutation cannot be targeted at the current time [9]. Clearly, further studies to identify novel targets in Xp11 translocation RCC are sorely needed.…”
Section: Introductionmentioning
confidence: 99%